2018
DOI: 10.17235/reed.2018.5263/2017
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal motor disorders are frequent during pre and post lung transplantation. Can they influence lung rejection?

Abstract: Background: lung transplantation (LTx) is a viable option for most patients with end-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Esophageal motor disorders such as distal spasm, hypercontractile esophagus and esophagogastric junction outflow obstruction were also observed more frequently post-lung transplant in the rejection group. This study supports the role of esophageal motor disorders leading to impaired esophageal clearance in the development of lung transplant rejection (20).…”
Section: Esophageal Disease After Lung Transplantationsupporting
confidence: 85%
“…Esophageal motor disorders such as distal spasm, hypercontractile esophagus and esophagogastric junction outflow obstruction were also observed more frequently post-lung transplant in the rejection group. This study supports the role of esophageal motor disorders leading to impaired esophageal clearance in the development of lung transplant rejection (20).…”
Section: Esophageal Disease After Lung Transplantationsupporting
confidence: 85%
“…Similarly, the study by Gor et al 28 showed that EGJ CI was 46.20 ± 7.60 in healthy controls vs 89.22 ± 33.26 for LT patients in our study. These results also go along with previous studies that supported increased EGJ competency after LT. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Esophageal dysmotility and gastroesophageal reflux (GER) are common in patients with respiratory disease, thought to be linked to disease progression, and are also common following LTx. The most common esophageal motor disorders include minor disorders of peristalsis, such as ineffective esophageal motility (IEM) and esophago-gastric junction outflow obstruction (EGJOO), [3][4][5][6][7][8][9] along with Jackhammer esophagus seen in some patients, mainly post-LTx, 4,[6][7][8][10][11][12] IEM is associated with greater numbers of proximal reflux events both in respiratory disease 9 and following LTx, 8 while EGJOO is associated with significantly less GER, despite an apparent increased risk of developing CLAD post-LTx. 8 Although studies have suggested that distal contractile integral (DCI) 4,6,7 and aperistalsis prior to LTx can improve following LTx, 13,14 it remains unclear whether certain motility diagnoses prior to LTx either remain the same or change to another diagnosis following LTx, and if this differs with type of respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…The most common esophageal motor disorders include minor disorders of peristalsis, such as ineffective esophageal motility (IEM) and esophago-gastric junction outflow obstruction (EGJOO), [3][4][5][6][7][8][9] along with Jackhammer esophagus seen in some patients, mainly post-LTx, 4,[6][7][8][10][11][12] IEM is associated with greater numbers of proximal reflux events both in respiratory disease 9 and following LTx, 8 while EGJOO is associated with significantly less GER, despite an apparent increased risk of developing CLAD post-LTx. 8 Although studies have suggested that distal contractile integral (DCI) 4,6,7 and aperistalsis prior to LTx can improve following LTx, 13,14 it remains unclear whether certain motility diagnoses prior to LTx either remain the same or change to another diagnosis following LTx, and if this differs with type of respiratory disease. Given the differential effects that dysmotility can have on esophageal exposure to reflux, better understanding of the changes in motility diagnosis following LTx may help to explain the current lack of clarity on the effect of LTx on GER, as attested by some studies reporting a worsening 15 but others no effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation